Tong : De slag om Roosendaal. - Van Damme, Jet; Schreurs, Lisette; Verster, Janine; Verbogt, Thomas; Serafijn, Q.S.; Roosendaal (Roosendaal : Stichting Int Heyderadey, 2001)
Assmann, Gijs ; Hoekstra, Berend ; Krebbekx, Judith ; Serafijn, Q.S. ; Vermeule, Koen
Roosendaal, 2001
kunstcatalogus